1994
DOI: 10.1111/j.1365-2559.1994.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

CD34 immunoexpression in stromal tumours of the gastrointestinal tract and in mesenteric fibromatoses

Abstract: The aim of this study was to explore whether CD34 immunoreactivity can distinguish between different types of gastrointestinal stromal tumour, i.e. smooth muscle and neurogenic. We studied 87 stromal tumours from different sites in the gastrointestinal tract, as well as the omentum and mesentery, using a monoclonal antibody to CD34 (QBEND10). We also determined the immunoexpression of smooth muscle and muscle specific actins, S-100 protein, cytokeratin, desmin and vimentin. In addition, 15 cases of mesenteric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 31 publications
2
45
1
5
Order By: Relevance
“…1,3,4,13,17,27,28 In our study, CD34 labeling was observed in most intestinal adenocarcinomas (5/7) and parathyroid neoplasms (2/2) and sporadically in apocrine gland neoplasms (2/6), squamous cell carcinomas (2/7), follicular neoplasms (1/5), and mammary carcinomas (1/14). In the sole thymoma, CD34 labeling was restricted to the neoplastic thymic epithelial cells (confirmed by immunohistochemistry for pancytokeratin).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…1,3,4,13,17,27,28 In our study, CD34 labeling was observed in most intestinal adenocarcinomas (5/7) and parathyroid neoplasms (2/2) and sporadically in apocrine gland neoplasms (2/6), squamous cell carcinomas (2/7), follicular neoplasms (1/5), and mammary carcinomas (1/14). In the sole thymoma, CD34 labeling was restricted to the neoplastic thymic epithelial cells (confirmed by immunohistochemistry for pancytokeratin).…”
Section: Discussionsupporting
confidence: 56%
“…well-characterized in human endothelial cell neoplasms 31 and in nonvascular neoplasms, such as human precursor lymphoid and myeloid neoplasms, 29,31 human and canine gastrointestinal stromal neoplasms, 8,9,17,19,32 and canine and feline meningeal neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Their origin remains unclear, although origin in smooth muscle cells has been proposed (Mikami et al, 1998;Saul et al, 1987). CD34-ir is often present in GIST (Erlandson et al, 1996;Miettinen et al, 1995Miettinen et al, , 1998Monihan et al, 1994;Sakurai et al, 1999), a property shared with various other solid tumors (Chaubal et al, 1994;Silverman and Tamsen, 1996). Kit-ir may be a suitable marker for GIST (Kindblom et al, 1998), possibly superior to CD34-ir .…”
Section: Gastrointestinal Stromal Tumorsmentioning
confidence: 99%
“…The finding that the majority of stromal tumors stained with CD34, a marker of myeloid progenitor cells, endothelial cells, and some mesenchymal lesions, helped separate GISTs from most true leiomyomas and schwannomas (which are CD34 negative; 4). CD34 positivity in GISTs ranges from 46 to 100%, depending on the site of origin of the tumor (4,5). The least CD34 positivity is seen in small-bowel GISTs (4).…”
mentioning
confidence: 99%